Spondylodiscitis in a healthy 12-year-old girl with Extraintestinal pathogenic Escherichia coli (ExPEC) bacteraemia - Gaschignard, J. (BMC Infect Dis, 2017)
BACKGROUND: Escherichia coli (E. coli) is rarely implicated in bone or joint infections in children. CASE PRESENTATION: We discuss the case of a healthy 12-year-old girl with an E. coli bacteraemia and a T11-T12 spondylodiscitis revealed by magnetic resonance imaging. The strain harboured serogroup O1:K1 and virulence factors common to highly virulent extra intestinal pathogenic E. coli (ExPEC). Immunological work-up was normal. CONCLUSION: The identification of E. coli in a spondylodiscitis should lead to the search for immunosuppression of the host and virulence factors of the strain, particularly those of ExPEC.